2001
DOI: 10.1212/wnl.57.2.196
|View full text |Cite
|
Sign up to set email alerts
|

Visual field constriction

Abstract: Accumulation of VGB in the retina, with or without an increase in GABA, may be responsible for the visual field constriction reported clinically. In contrast, TGB had no effect on GABA concentrations and did not accumulate in the retina. These results suggest that TGB is unlikely to cause visual field defects in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 41 publications
3
51
1
Order By: Relevance
“…Although another study found no retinal lesions after administering VGB orally for 1 year to CD[SD]BR (albino) rats, this study also hypothesized that light has a critical role in VGB retinotoxicity (28). Finally, because GABA can be toxic to neurons (29,30), VGB retinotoxicity may stem from higher retinal GABA levels (25,26).…”
mentioning
confidence: 70%
See 3 more Smart Citations
“…Although another study found no retinal lesions after administering VGB orally for 1 year to CD[SD]BR (albino) rats, this study also hypothesized that light has a critical role in VGB retinotoxicity (28). Finally, because GABA can be toxic to neurons (29,30), VGB retinotoxicity may stem from higher retinal GABA levels (25,26).…”
mentioning
confidence: 70%
“…We used 500 µM VGB as a test concentration because it is in the range needed to obtain electrophysiologic effects in hippocampal slices (31) and is well below the ≥1 mM concentrations achieved in the retina 2 to 4 h after Sprague-Dawley rats receive an intraperitoneal injection of 1,000 mg/kg VGB (25,26). By light microscopy, isolated retinas incubated with ≤500 µM VGB for 20 h in the dark showed no histologic change (Fig.…”
Section: Ex Vivo Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical application of VGB has been drastically limited after the observation that the drug irreversibly restricts the peripheral visual field in patients receiving VGB (Lawden et al, 1999;Wild et al, 1999). Experimental studies on rats have indicated that VGB preferentially accumulated in the retina reaching concentrations five-fold higher than in the brain, which was additionally associated with a threefold increase in GABA levels in the retina (Sills et al, 2001).…”
Section: Introductionmentioning
confidence: 99%